Motions in Pictures: From Habermas’s Informal Political Sphere to Formal Politics in the Films Footloose, Land and Freedom and The Beguiled - Jane Thomas; Sean Tunney (Humanities)
This article analyses three historical fiction films, Footloose, Land and Freedom and The Beguiled, to help illuminate aspects of politics and political theory. We study them to explore the relationship between Habermas’s concepts of the lifeworld and political spheres, which analysts have critiqued as opaque. Drawing on Habermas’s theory of communicative action, we debate prevailing understandings of the implications of his work for deliberative democracy via an exploration of the films. By expanding the definition of the term ‘motion’ (otherwise known as ‘draft resolution’), we relate this concept to these Habermasian themes. Thus, this paper analyses feature film case studies as they incorporate motions into fictionalised accounts. We suggest that focusing on these movies’ motions, embedded in unfolding narratives, can help reconceive Habermas’s work to illustrate fluidity in how people and ideas may move between informal and more formal spheres. Ultimately, by showcasing the importance of motions in political participation, via these movies, we advance the idea that motions may be seen as part of a ladder of involvement, providing further opportunities for encouraging participation.